Surface Performance of Titanium Alloy Brake Shell Polished by Industrial Robot Based on Digital Twin - Haijun Zhang; Shengwei Chen; Hui Wang; Yan Qin (International Journal of Aerospace Engineering)
The titanium alloy brake shell is an important component used in aviation, but its surface polishing is mostly done manually, making it difficult to ensure surface quality and consistency. As a result, an industrial robot polishing system based on digital twin is proposed, which can realize the interaction between physical and virtual platforms by using digital twin technology, acquire various parameters in real time, and monitor the polishing process. Based on this system, a removal depth model was established, and the polishing parameters to be analyzed were determined by combining the removal depth model. On this basis, the influence law of polishing parameters on surface roughness is analyzed through physical tests, and orthogonal experiments are used to optimize the polishing parameters. The results show that the surface roughness is reduced to 0.171 μm after optimization. Finally, the reliability of the polishing system is verified through the polishing machining test, and the surface quality of titanium alloy brake shell is significantly improved.